DEVELOPMENT OF SOCIAL STUDIES LEARNING VIDEOS GEOGRAPHY MATERIALS BASED ON LOCAL WISDOM AS SOURCES AND SOCIAL STUDIES TEACHING MATERIALS - ROHMAN, SLAMET; RIDWANUDIN LAILI, MUCHAMAD (Journal Civics And Social Studies, 2025)
This study aims to develop and analyze the effectiveness of using social studies educational videos on geography material that integrates local wisdom content as a source and teaching material for social studies. The cultural wealth and local wisdom Indonesia possesses must be understood and learned by students. By integrating local content into social studies learning in geography, students' understanding of the local environment and culture can be enriched. This research method uses a research and development (R&D) approach, beginning with the video production process, validation testing by subject matter and media experts, and limited testing with students and teachers at SMPN 1 Rancah, Ciamis Regency, as the research subjects. The research results indicate that the developed educational videos not only increase students' interest in learning but also deepen their understanding of geography-based content rooted in local wisdom. Students responded positively to the use of this video, indicating that integrating local wisdom into geography material in social studies education can enhance the relevance of the material to students' daily lives. Based on the perceptions of IPS teachers at SMPN 1 Rancah, Ciamis Regency, the developed educational video has proven to be an effective medium for delivering material in an engaging, interactive, and user-friendly manner. Thus, the IPS educational video on geography based on local wisdom holds significant potential as an innovative and relevant learning resource in the context of IPS geography education in the current digital era. Keywords : Social Studies Learning Videos, Geography, Local Wisdom, Social Studies Teaching Resources and Materials